Pictorial Representation of Ideology Found in “English For Change” EFL Textbook - Fikri, Abdul (Universitas Nurul Jadid, 2024)
The ideology shaped all aspect of human life. In controlling the society, the government placed the ideology in the textbook as a part of education. This research aimed to identify pictorial representation of ideology found in “English for Change” EFL textbook. This research is a qualitative research. The data of this research were collected from “English for Change” EFL textbook. The result of this research revealed that there were 13 pictorial representation of ideology. The frequent pictorial representation of ideology was Pancasila with 12 pictorial representations. It was then followed by Bhinneka Tunggal Ika value with 1 pictorial representation. The emphasis on Pancasila rather than Bhinneka Tunggal Ika in the textbook indicates a purposeful focus on the broader principles and values of Pancasila to guide students' grasp of Indonesian ideology.